Anticancer activity of eugenol is not related to regulation of the oncogenic transcription factor Forkhead Box M1 - Wiirzler, Luiz Alexandre Marques; Aguiar, Rafael Pazinatto; Bersani-Amado, Ciomar Aparecida; Velázquez-Martínez, Carlos Alberto; Cuman, Roberto Kenji Nakamura (Acta Scientiarum. Health Sciences, 2016)
Genome-wide gene expression profiling of cancers has consistently identified the FOXM1 as one of the most commonly upregulated genes in cancer cells that plays an essential role in the regulation of a wide spectrum of biological processes, including inhibition of apoptosis. Since the anticancer activity of EUG reported in the literature is related to induction of apoptosis in cancer cells, we hypothesized that there is a correlation between the EUG-induced apoptosis effect and downregulation of FOXM1. A series of experiments were conducted to evaluate the effect of EUG on cellular viability of cancer cells (MTT) and its potential regulatory effect on FOXM1 protein levels (western blots). Our findings confirm the anticancer effect of EUG on different human cancer cell lines as previously reported in the literature (SKBR3 LC50: 318.6; HT29 LC50: 525.5; and HepG2 LC50: 2090.0 µM). However, we demonstrated that EUG does not regulate the FOXM1. The results evidenced the anticancer effect of EUG on three cancer cell lines and showed that the EUG- apoptosis induced effect is not related to regulation of FOXM1 at the protein level. Further studies must be done to provide information on the mechanism of action of this agent.